Intracellular modulation of alpha7 ionotropic and metabotropic functions by tyrosine phosphorylation - Chrestia, Juan Facundo (2019)
The α7 receptor is a nicotinic receptor present in neuronal and non-neuronal cells. α7 acts as a ligand-gated ion channel and as a metabotropic receptor. We investigated the role of tyrosine phosphorylation of the intracellular domain (ICD) in the dual ionotropic/metabotropic receptor function. Single-channel recordings from HEK cells expressing α7 showed that channel activity appears as brief isolated openings and episodes of few openings in quick succession (bursts). Exposure to an inhibitor of Src family kinases (PP2) increased the frequency and duration of bursts while preincubation with an inhibitor of tyrosine phosphatases had the opposite effect. Co-expression of α7 and an inactive Src kinase also increased burst duration. A mutant α7 lacking tyrosine phosphorylation sites in the ICD showed longer burst durations and insensitivity to PP2, thus recapitulating the effects of phosphorylation inhibition on wild-type α7. Cells exposed to the specific α7 agonist (PNU-282987) showed an increase of ERK1/2 phosphorylation, which was abolished by exposure to a tyrosine kinase inhibitor. PNU-282987 did not trigger ERK phosphorylation in cells expressing the mutant receptor lacking tyrosine residues or co-expressing α7 and α7-ICD domain. Our results indicate that dephosphorylation positively modulates ionotropic α7 activity in a way compatible with decreased desensitization, and that the phosphorylated state of α7-ICD plays a role in metabotropic receptor responses.